Stastical approaches to optimize tissue culture conditions for secondry metabolite production of Phyllanthus pulcher wall. ex mull. arg. - Danaee, Mahmoud (2013)
Medicinal plants are rich sources of bioactive compounds, which are being used in pharmaceutical industries. To date, due to commercial exploitation there is an acute shortage of population in their natural habitats. Domestication and cultivation is often difficult due to agro-climatic constraints. Hence, the production of secondary metabolites via the cultivation of plants through new technologies such as tissue culture, including through advanced bioreactor is the way forward. In this study,Phyllanthus pulcher an important medicinal plant was used to establish tissue culture system through the use of statistical models for estimation of secondary metabolites via manipulation of media, elicitors and plant growth regulators. Three selected accessions out of 35 accessions maintained in the field AGRO-GENE BANK Department of Crop Science (UPM) were screened for secondary metabolites following which accession 11383 was selected and used for tissue culture experiments which consisted of establishment of sterilization protocol, callus induction, media optimization, elicitors and PGRs effects. Sterilization protocol was established using Clorox and Ethanol. The results revealed that the best method for leaf explants was the application of 15% Clorox for 15 minutes followed by immersion in 70% Ethanol for 1 min. To induce callus, the best result was observed on the leaf explant at 30 mgL-1 of 2, 4-D. After inducing the callus, effects of four types of media (Murashinge-Skoog, B5, DKW and WPM) at three different strengths (half , full and 1.5 strength) and 3 harvesting times (15, 30 and 45 days) on callus growth and secondary metabolites production were studied under both solid and liquid cultures. The results of this study showed that for both solid and liquid cultures, the highest secondary metabolites were produced in full strength WPM and 1.5 strength WPM respectively. The effects of carbon were investigated using three different sources of carbon (fructose, glucose and sucrose) at three concentrations (1, 2, and 3 %). Results showed that sucrose at 3% had significantly higher secondary metabolites content. To determine the effects of PGRs, different concentrations of BAP was applied with two kinds of auxin (NAA and 2, 4-D). Secondary metabolites content as well as callus growth were improved when 2 mgL-1 BAP and 2 mgL-1 NAA were applied on the callus for 30 days. The effects of Methyl jasmonate (MeJA) and Salicylic acid (SA) as two abiotic elicitors were evaluated for growth and secondary metabolite production of callus culture in P. pulcher. The results revealed that high concentration of MeJA (> 10 mM) inhibits the callus growth. The results further revealed that 1 mM of MeJA resulted in the highest yield for total flavonoid and phenolic contents. Applying SA also improved the secondary metabolite content while in higher concentrations (> 50 mgL-1) all samples died. In the final section of this research based on findings of previous experiments and understanding of effective nutritional factors, PGRs and elicitors a Central Composite Design (CCD) was conducted. The experiment included 54 runs with different combinations of N, Ca, K, P, sucrose and SA. The data of this experiment were analyzed using Response Surface Methodology (RSM) and Artificial Neural Network (ANN) the result showed that ANN models are more flexible and adaptable for prediction of secondary metabolite production in plant cell culture. Results indicated that flavonoid and phenolic production in ANN model prediction were higher than RSM prediction 4% and 19.6% respectively, while factors such as N, Ca,K and SA had a lower concentration in ANN than RSM estimation.